2023
DOI: 10.3389/fnut.2023.1098761
|View full text |Cite
|
Sign up to set email alerts
|

Associations of dietary antioxidant micronutrients with the prevalence of obesity in adults

Abstract: BackgroundAntioxidant micronutrients have a therapeutic potential for clinical treatment of obesity. NO research, however, has examined the connection between the complex level of dietary antioxidants and obesity.Materials and methodsWe mainly aimed to investigate the relationship between a combination of antioxidants and obesity using the database of the national health and nutrition examination survey (NHANES). This cross-sectional study contains a survey of 41,021 people (≥18 years) in total ranging from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Furthermore, a previous NHANES study also reported that the Se dietary intake was unrelated to the BMI and WC [37]. Nevertheless, another study revealed a positive correlation between Se dietary intake and obesity in adults [38].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a previous NHANES study also reported that the Se dietary intake was unrelated to the BMI and WC [37]. Nevertheless, another study revealed a positive correlation between Se dietary intake and obesity in adults [38].…”
Section: Discussionmentioning
confidence: 89%
“…Vitamin C has been found to scavenge free radicals and suppress lipid peroxidation, which can lead to decreased vitamin C levels in obese individuals due to increased body fat and oxidative stress (Y. Yang et al, 2023). Vitamin C may inhibit metabolic changes induced by certain stressors like high-fat diets, with studies showing that high doses of vitamin C can induce weight loss safely in obese individuals (Yuan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that the rate of increase in obesity is greater in regions of the world with greater micronutrient deficiencies [17], while others reported significant inverse associations between the dietary intake of micronutrients and Body Mass Index (BMI) and/or obesity [18][19][20][21][22]. These studies were cross-sectional and hence failed to demonstrate the cause-and-effect relationship between micronutrient deficiencies and excess weight unequivocally.…”
Section: Effects Of Micronutrient-deficient Diet On Obesitymentioning
confidence: 99%